A novel, liposome-loaded, injectable hydrogel for enhanced treatment of choroidal neovascularization by sub-tenon's injection. (December 2022) - Li, J.; Tian, Q.; Sun, H.; Zhang, Y.; Yang, X.; Kaur, P.; Wang, R.; Fang, Y.; Yan, H.; Du, X.; Ye, L.; Zhai, G.
Abstract: As a common multifactor fundus lesion, choroidal neovascularization (CNV) has become the leading cause of severe vision loss in the elderly. The mainstay treatment is an invasive intravitreal injection of anti-VEGF drug, which leads to a short half-life, incomplete response, and severe ocular complications. In this work, we have developed a novel, liposome-loaded, injectable hydrogel (cSA@Lip-HAC) by a minimally invasive sub-tenon's injection for CNV treatment. First, the multitarget angiogenic inhibitor (sunitinib) and hypoxia-inducible factor inhibitor (acriflavine) were co-loaded in the liposome, which was then loaded in the injectable hydrogel. The in vitro results showed that the cSA@Lip-HAC group had a strong anti-angiogenesis effect. After sub-tenon's injection, the hydrogel endowed the drug-loaded liposome with a longer retention time in the target area. In the CNV model, cSA@Lip-HAC showed a significant anti-CNV effect, which was superior to that of intravitreal injection of a commercial product (Conbercept). Exploration of the molecular mechanism revealed that cSA@Lip-HAC did not only inhibit CNV through the AKT/mTOR/HIF-1α/VEGF signal pathways but also inhibit VEGF R1 and VEGF R2. In conclusion, this novel drug delivery system, combining the merits of the liposome and hydrogel, showed an enhanced anti-CNV effect, thus providing a new and minimally invasive alternative for the treatment of neovascular ocular diseases.